Study on the Satisfaction Factors of College Selection for International Students and Pre-educated Local Education Center Students - 장선영; 윤태훈 (International Journal of Advanced Culture Technology(IJACT), 2019)
As the attracting foreign student has become a very important strategy, detailed researches on their college selection and their satisfaction with college life are needed. Especially it is necessary to distinguish ordinary international students and those who take classes in Local Education Centers (LEC) before coming to Korea. The central purpose of this study is to identify how the two types of students differ in their perception of college selection factors and what factors affect their satisfaction with college life. A total of 186 international students participated in the study. It was found that the most important college selection factor of the pre-educated LEC students was ‘obtaining academic ability through online classes and transfer of credit hours’. Second, these students reported that the two influential factors for their satisfaction with college life were 'quality of education' and 'cultural experience program'. Third, it was found that the major college selection factors influencing ordinary international students’ college life satisfaction were 'expertise of faculty', ‘transfer of credit through curriculum links', and 'recommendation from teachers at home country'. Fourth, the major factors affecting the pre-educated LEC students’ satisfaction with college life were 'KSL classes at LE’s’, ‘expertise of faculty', and ’financial aid system'.